Cerebral microbleeds and structural white matter integrity in patients with traumatic brain injury : a diffusion tensor imaging study - Dahl, Juho (My University, 2022)
Diffuse axonal injury (DAI) is a common neuropathological manifestation of traumatic brain injury (TBI), presenting as alterations in the cerebral white matter (WM) microstructure and often leading to long-term neurocognitive impairment. Cerebral microbleeds (CMBs) are a common finding on head imaging in TBI and are often considered a visible sign of DAI, although they represent diffuse vascular injury. It is poorly known how they associate with long-term white matter integrity. This study included 20 patients with TBI and CMBs, 34 patients with TBI without CMBs, and 11 controls with orthopedic injuries. CMBs were detected using susceptibility-weighted imaging (SWI), graded according to their location in the WM and total lesion load was counted. Patients underwent SWI within two months after injury. Diffusion tensor imaging (DTI) was used to assess microstructural WM alterations at an average of eight months after injury. We found that CMB grading and total lesion load were negatively associated with fractional anisotropy (FA) and positively associated with mean diffusivity (MD). Patients with TBI and CMBs had decreased FA and increased MD compared with patients with TBI without CMBs. When adjusting for the clinical severity of the injury, none of these associations were found. Thus, the difference in FA and MD is explained by patients with TBI and CMBs having more severe injuries. Our results suggest that CMBs are not associated with greater WM alterations when adjusting for the clinical severity of TBI. Thus, CMBs and WM alterations appear to represent independent aspects of TBI.
Keywords: traumatic brain injury, white matter, cerebral microbleeds, diffuse axonal injury, diffusion tensor imaging